2011
DOI: 10.1002/ppul.21468
|View full text |Cite
|
Sign up to set email alerts
|

Airway refractoriness to inhaled mannitol after repeated challenge

Abstract: Exercise and inhaled mannitol are thought to cause bronchoconstriction through a similar mechanism in asthma. The response to exercise becomes refractory with repeated challenges. This study aimed to investigate whether repeated challenge with mannitol induces refractoriness, as with exercise. Forty-one children with asthma underwent two consecutive dose-response mannitol challenges (Phase 1); the second challenge proceeded after recovery (FEV(1) : 95% or more of baseline value) from the first. The response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The decrease in airway responsiveness to mannitol at 24 h post–allergen challenge is likely not explained by a refractory or cross‐refractory mechanism as the reported duration of refractory periods ranges from 1 to 2 h for exercise‐induced bronchoconstriction , 2–8 h for adenosine‐5′‐monophosphate (AMP) , and up to 2 h for mannitol . We are unaware of a refractory state with respect to repeat allergen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in airway responsiveness to mannitol at 24 h post–allergen challenge is likely not explained by a refractory or cross‐refractory mechanism as the reported duration of refractory periods ranges from 1 to 2 h for exercise‐induced bronchoconstriction , 2–8 h for adenosine‐5′‐monophosphate (AMP) , and up to 2 h for mannitol . We are unaware of a refractory state with respect to repeat allergen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the early asthmatic response to a second allergen challenge was unchanged compared to that of the first challenge indicating a refractory state does not develop when allergen challenges are performed 24 h apart. Refractoriness is common with non-allergic indirect acting stimuli including exercise [ 6 ], adenosine monophosphate [ 7 ] and mannitol [ 8 ]. Cross refractoriness has also been shown between exercise and metabisulphate [ 9 ], exercise and AMP [ 11 ] and allergen and mannitol [ 5 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…By definition, the bronchoconstriction caused by allergic stimuli occurs through an indirect mechanism. A phenomenon commonly seen with indirect acting stimuli is refractoriness [ 5 8 ]. Refractoriness refers to a diminished airway response to a given stimuli when a subsequent challenge is performed within a relatively short time frame (e.g.…”
Section: Introductionmentioning
confidence: 99%